FACTORIAL MODEL OF ENTERPRISE STABLE DEVELOPMENT - N. V. Golovkova (Наука и техника)
The paper considers and analyzes a number of methodological approaches to definition of enterprise stability. The basic distinctive features of such terms as “economic steadiness” and “economic stability” are highlighted, the essence and contents of the concept “stability of development” are determined. Classification of factors influencing on enterprise stability is offered with due account of certain conditions and economic situations. The described factorial model for determination of enterprise stability extent is based on the results of research at the enteфrises in the Republic of Belarus. Calculation of a factorial exponent of stability with the account of the most significant factors rendering influence on stability of an industrial enterprise is executed. It is substantiated that an enterprise is considered as a stable one if its factorial exponent of stability tends to the highest estimation 100.